Prevalence Of Piriformis Syndrome In Housekeeping Staff - More, Kinjal; Patil, Maithili; Misal, Kareena (Journal of Neonatal Surgery, 2025)
Background: In the area of glutes, the piriformis muscle plays vital for hip rotation and stability. Jobs involving long periods of standing and physically demanding work causes syndrome and fatigue due to sustained pressure. Piriformis syndrome, pressurizes sciatic nerve, drastically causing pain, uneasiness, and restricted movement. This results in chronic musculoskeletal strain and impact productivity and overall well-being. Methods: Housekeeping staff having significant clinical features underwent evaluation of NPRS, examining tightness by seated piriformis stretch test and buttock pain by FAIR test were recorded. Age, years of experience and duration of work was taken into consideration. Patients with back surgery, trauma, arthritis and spinal deformities were excluded. Result: In this study 80 participants, higher prevalence of piriformis syndrome was observed in participants aged 25- 45 years, with mean age 34.83 (±6.09). The NPRS indicated that 62.5% had mild pain at rest, while 46.25% reported severe pain during movement. 61.25% subjects resulted positive for seated Piriformis Stretch test and FAIR Test, with a higher percentage of females (71.19%) testing positive compared to males (33.33%). Conclusion Patients daily lives are greatly affected by hip discomfort, as many find it difficult to carry out fundamental activities because of the pain. The elevated occurrence of affirmative Seated Piriformis and FAIR test outcomes piriformis syndrome. The considerable pain underscore the necessity for enhanced management approaches. Investigating gender differences and the root causes of hip discomfort in greater depth would assist in more effectively customizing treatments.